PEMERIKSAAN URINALISIS UNTUK MENENTUKAN STATUS PRESENT KAMBING KACANG (Capra sp.) DI UPT HEWAN COBA FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS SYIAH KUALA (Urinalysis Examination to Determine Present Status of Local Goats (Capra sp.) at UPT Experimental Animals Faculty of Veterinary Medicine Syiah Kuala University) - Emilaza Pratama; Rusli Rusli; Zuraidawati Zuraidawati; Nuzul Asmilia; Roslizawaty Roslizawaty; Zuhrawati Zuhrawati (Universitas Syiah Kuala, 2016)
This research was aimed to determine the present status of local goats based on the age at UPT experimental animals Faculty of Veterinary Medicine Syiah Kuala University by urine examination. Sample used in this research was urine from 13 local goats (Capra sp.) male and female that collected in the morning. Dipstick urine (Verify TM) was directly dipped into the collected urine and the result were obtained by comparing with a standard color on urine dipstick (Verify TM) with interval 30-120 seconds. The semiquantitatively data obtained using urine dipstick include measurement of leukocyte, nitrite, urobilinogen, protein, pH, blood in the urine, specific gravity, ketones, bilirubin and glucose. From the results obtained age 1 year nitrite 1 goat, blood 1 goat, alkaline pH and density under normal circumstances. At the age of 1-3 years old goats there are leukocytes 4 goats, nitrite 2 goats, proteins 4 goats, bilirubin 1 goat, pH is alkaline and density under normal circumstances. In goats aged 3-4 years there is leukocytes 1 goat, nitrite 2 goats, pH is alkaline and density under normal circumstances.